ADOPTION OF AUDIT SOFTWARE: BENEFITS, CHALLENGES, AND STRATEGIES - Wan Ahmad, Wan Noraswaniaty; Zakaria, Maheran (Journal of Islamic, Social, Economics and Development, 2024)
The swift advancement of digital technologies is reshaping the field of auditing and offering various opportunities as well as challenges. Professional bodies such as the International Federation of Accountants (IFAC), Auditing and Assurance Standards Board (IAASB) and the Malaysian Institute of Accountants (MIA) have promoted the integration of digital tools to enhance audit practices. Audit software, one of the elements of Computer-Assisted Audit Tools and Techniques (CAATTs), has significantly transformed the auditing landscape by enhancing accuracy, improving efficiency, and expanding data analysis capabilities. While large audit firms have successfully integrated and are reaping the benefits of adopting audit software, smaller firms often face difficulties due to high implementation costs, technical complexities, and resistance to change. Hence, this paper focused on the audit software adoption benefits, its challenges and proposed strategies to enhance the adoption of this technological tool. Raising awareness, simplifying implementation, offering comprehensive training, fostering organizational support, and enhancing security measures are essential steps to bridge the digital divide in the auditing profession. These strategies offer valuable information into audit software adoption as to enhance audit quality and effectiveness, ensuring the profession keeps pace with technological advancements.